Philosophy for Children (P4C): A New Zealand School-based Action Research Case Study - Leon Benade (New Zealand Journal of Teachers' Work)
This paper considers whether Philosophy for Children (P4C) can contribute to the development of the ‘thinking’ key competency of The New Zealand Curriculum. Additionally, it seeks to demonstrate what ‘action research’ looks like in relation to a seven month trial in a New Zealand school of P4C and its associated methodology of the Community of Philosophical Enquiry (COPE). The action research methodology outlined here is broadly a form of practitioner enquiry, which affirms the role of the researcher, thus breaking with conventional positivistic and rationalist research that hides the researcher from view. Several data sources are tracked to reach the conclusion that P4C does indeed encourage critical thinking and deep questioning – but not for all students, and not to the same extent for all in this study, thus creating a new ‘problem’. The mixed success of the trial suggests good grounds for further exploration of the practice of P4C in schools such as that under study here.